1988
DOI: 10.1530/jrf.0.0840023
|View full text |Cite
|
Sign up to set email alerts
|

Urinary steroid concentrations during natural and gonadotrophin-induced oestrus and pregnancy in the giant panda (Ailuropoda melanoleuca)

Abstract: Urinary concentrations of conjugated oestrone and pregnanediol-3-glucuronide were measured during and after spontaneous and induced oestrus and during pregnancy. Behavioural oestrus was preceded by a rise in oestrone values from less than 10 ng/mg creatinine (Cr) to peaks of 45 ng/mg Cr. Maximal lordotic response and mating activity coincided with the decline in oestrone levels. After presumed ovulation, urinary pregnanediol glucuronide concentrations increased from less than 5 to 15-30 ng/mg Cr. Further incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 12 publications
10
46
0
Order By: Relevance
“…Although some studies contest this argument (Göritz et al 1997), our results suggest that this may be the case in giant pandas because of the significant relationships we found between peak progesterone and subsequent fetus detection. The delay that we found in the peak progesterone level of the pregnant female giant pandas, accompanied by a relatively unvarying window between the time of peak progesterone to parturition, also supports previous studies done on single pregnant giant panda females (Chaudhuri et al 1988, Monfort et al 1989). If we assume that the giant panda embryo is implanted around the time the peak in urinary progesterone level occurs, then, according to our results, the period of delayed implantation in giant pandas is around 107.15G19.75 days.…”
Section: Characterizing Delayed Implantation In Giant Pandassupporting
confidence: 91%
See 1 more Smart Citation
“…Although some studies contest this argument (Göritz et al 1997), our results suggest that this may be the case in giant pandas because of the significant relationships we found between peak progesterone and subsequent fetus detection. The delay that we found in the peak progesterone level of the pregnant female giant pandas, accompanied by a relatively unvarying window between the time of peak progesterone to parturition, also supports previous studies done on single pregnant giant panda females (Chaudhuri et al 1988, Monfort et al 1989). If we assume that the giant panda embryo is implanted around the time the peak in urinary progesterone level occurs, then, according to our results, the period of delayed implantation in giant pandas is around 107.15G19.75 days.…”
Section: Characterizing Delayed Implantation In Giant Pandassupporting
confidence: 91%
“…The reason is that like other ursids, giant pandas may exhibit a phenomenon known as delayed implantation, in which the embryo floats in the womb and arrests development until it attaches to the uterus months later. Delayed implantation is believed to occur in giant pandas based on hormone analyses (Hodges et al 1984, Chaudhuri et al 1988 and the observed discrepancy between the panda's long gestation coupled with underdeveloped young (Zhu et al 2001). This physiological response is believed to be seasonal and could be an adaptation to an unpredictable food source that would make it advantageous for the birth of the offspring to match a time of highest availability of food sources (Mead 1989, Sandell 1990.…”
Section: Introductionmentioning
confidence: 99%
“…This interval was then followed by a distinctive 3-to 20-fold elevation that lasted another 28-63 days before declining to signal birth or the end of a non-parturient phase. A general biphasic progestagen pattern has been reported from earlier urinary monitoring studies of this species, but only in a few individuals (Hodges et al 1984, Chaudhuri et al 1988, Masui et al 1989, Monfort et al 1989, Mainka et al 1990, McGeehan et al 2002, Narushima et al 2003. The present study was important because of the increased confidence generated from simultaneously examining a large cohort of giant pandas, some of which were observed year to year.…”
Section: Discussionmentioning
confidence: 72%
“…There has been little attention directed at understanding the prolonged luteal phase in pregnant versus non-pregnant individuals. Of ten reports on this topic, only three giant pandas in total have been monitored for urinary progestagen profiles from ovulation to parturition or through a non-parturient phase (sometimes referred to as 'pseudopregnancy'; Bonney et al 1982, Hodges et al 1984, Chaudhuri et al 1988, Masui et al 1989, Monfort et al 1989, McGeehan et al 2002, Narushima et al 2003, Dehnhard et al 2006, Steinman et al 2006, Spady et al 2007. In these cases, a secondary urinary progestagen rise has occurred 74-122 days after the end of oestrus (Steinman et al 2006) that has suggested a shift in hormonal source, perhaps related to nidation.…”
Section: Introductionmentioning
confidence: 99%
“…Since neo-natesneonates are so altricial, weighing only about 100g and being only 15-17cm long, pandas evidently have a delay in implantation of the blastocyst (a gestation of 45 days would be sufficient for the observed development of the neonate) (Schaller et al 1985). Temporal changes in concentrations of various hormone and steroid conjugates in the urine also indicate delayed implantation Chaudhuri et al 1988;Monfort et al 1989). There is some evidence that females can experience spontaneous pseudopregnancy during the period prior to implantation (Monfort et al 1989;Mainka et al 1990).…”
Section: Sa Mainkamentioning
confidence: 99%